Pengaruh Beban Kerja Dan Konflik Kerja Terhadap Turnover Intention Pada Pt. Surganya Motor Indonesia Cabang Surabaya - Cahyanto, Edwin Dwi; Julindrastuti, Dijah (PRAGMATIS, 2022)
The purpose of this study is to look at how workload and workplace conflict affect employees' intentions to leave their jobs at the PT Surganya Motor Indonesia branch in Surabaya. Workload, work conflict, and turnover intention are the three variables included in this study. The investigation examines 90 samples using a quantitative methodology. Questionnaires are used to gather data, and random sampling procedures are used to choose the sample. Multiple linear regression analysis is the technique used for the analysis. As shown by a beta value of -1.141 and a Sig. Level of 0.070, the results of the research show that workload has no discernible influence on turnover intention. Work conflict, on the other hand, is discovered to have an impact on turnover intention, with a beta value of 0.170 and a Sig level of 0.012. An F value of 4.547, a Sig. level of 0.013, and an Adjusted R Square value of 0.074, or a 7.4% effect, show that workload and work conflict both influence turnover intention when taken into account concurrently